Penerapan Inovasi Pelayanan Publik Seblak Pedes Berbasis E-Government di Kantor Kecamatan Ngoro, Kabupaten Jombang - Ria Fauziah; Dewi Fitrotus Sa’diyah; Yuni Lestari; Dian Arlupi Utami; Nabila Septia Rosa (Policy and Maritime Review, 2026)
Public service innovation is a step toward improving the quality of services provided to the public. This study aims to analyze the implementation of the e-government based Seblak Pedes public service innovation at the Ngoro Subdistrict Office in Jombang Regency. The background for this study is the discrepancy between the objectives of the Seblak Pedes innovation and the reality on the ground. This study employs a qualitative approach using a descriptive method. In its implementation, the study draws upon e-government theory grounded in the key elements of successful e-government development, as identified by the Harvard JFK School of Government. This theory encompasses three main elements: Support, Capacity, and Value. Data were collected through interviews, observations, and documentation. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Seblak Pedes public service innovation has not yet been optimal. Regarding the Support element, outreach was conducted only during the Seblak Pedes launch and was directed solely at village officials rather than the general public, and was subsequently carried out only through social media. Regarding the Capacity element, the availability of forms remains limited, and there is a shortage of human resources. Regarding the Value element, some members of the public still do not fully perceive the benefits of the Seblak Pedes innovation.